Effects of aerobic and resistance exercise on glycosylated hemoglobin - Chou, Ying-Hsiang; Cheng, Yung-Yin; Nfor, Oswald Ndi; Chen, Pei-Hsin; Chen, Che-Hong; Chen, Hsin-Lin; Chang, Bo-Jiun; Tantoh, Disline Manli; Huang, Chien-Ning; Liaw, Yung-Po (PloS one, 2022)
Glycosylated hemoglobin (HbA1c) reflects the average blood sugar over the past eight to twelve weeks. Several demographic and lifestyle factors are known to affect HbA1c levels. We evaluated the association of HbA1c with aerobic and resistance exercise in non-diabetic Taiwanese adults based on the waist-hip ratio (WHR). We conducted this study based on TWB data collected from 90,958 individuals between 2008 and 2019. We estimated the Beta ([beta]) coefficient and 95% confidence intervals (CI) for HbA1c using multivariate regression models. Based on the multivariate analysis, lower HbA1c levels were associated with both resistance exercise ([beta]-coefficient = -0.027, 95% CI -0.037 to -0.017) and aerobic exercise ([beta]-coefficient = 0.018, 95% CI, -0.023 to -0.013). Higher HbA1c levels were associated with abnormal WHR compared to normal WHR ([beta]-coefficient = 0.091, 95% CI, 0.086 to 0.096). We detected an interaction between exercise and WHR (p for interaction = 0.0181). To determine the magnitude of the interaction, we performed additional analyses (with the reference group being 'abnormal WHR with no exercise') and observed substantial decreases in HbA1c regardless of the WHR and exercise category. However, the largest reduction occurred in the 'normal WHR and resistance exercise' group ([beta] = -0.121, 95% CI, -0.132 to -0.109). We found that normal resistance exercise, coupled with a normal WHR was significantly associated with lower HbA1c levels among non-diabetic individuals in Taiwan.